Hungary : Report on the Observance of Standards and Codes; FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This report examines Hungary's Observance of Standards and Codes on the Financial Action Task Force (FATF) recommendations for Anti-Money Laundering (AML) and Combating the Financing of Terrorism. Hungary has a substantial AML legal and institutional framework for combating money laundering (ML), including preventive measures for a wide range of service providers and law enforcement measures. The ML offense, while it addresses self-laundering, covers only using the proceeds of crime in the business activity of the perpetrator or in a bank or financial transaction.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet